Optimizing multi-channel use in digital marketing campaigns - Lemos, André Miguel Fonseca (2015)
Digital marketing has been gaining importance in the last years. It has become an easier, faster and more accountable way to reach customers than traditional, offline marketing, leading to more effective results and lower campaign costs. In digital marketing, the need to constantly reach large audiences is met by integrating online communication channels, as this increases customer touch points and ad exposures. It becomes thus important to know which channels perform better, individually or in combination with each other and traditional media. This dissertation evaluates the performance of different online advertising channels, including email (old/new formats), display (customary and social media formats) and search engine marketing (SEM), within a single, multi-channel campaign conducted in Portugal in 2014 for a large FMCG brand. First, the effectiveness and efficiency of different channels were statistically compared, and related to international benchmarks. Then, linear regression models were ran to estimate the effect of single and multiple channel use on campaign performance metrics. Results showed that classic email formats performed the best in terms of conversion rates, profit and ROI, whereas social media display ads performed the worst. Meanwhile, the use of SEM and new email formats did not improve campaign performance. It was possible to conclude that pre-defining and aligning campaign goals between agencies and advertisers is the key to optimize multi-channel use in digital marketing, as well as past experience with different channels.